DEVELOPMENT OF SCREENING METHOD OF FOOD ADDITIVES SAFETY AGAINST M2 MUSCARINIC RECEPTOR BY IN SILICO METHOD - Novitasari Turnip, Ruth
Food Additives (FAs) are substances needed in the manufacture of processed food. Therefore, prior their use, the safety, efficacy, and quality of FAs must be assured. Initial safety assessment of these substances can be carried out by means of their interactions with various relevant biological targets. Muscarinic receptors (M2) have a key role in modulating cardiac function and other important central processes, and hence a relevant biological target in the safety assessment of substances. The aim of this study was to obtain a screening method to evaluate the safety of FAs by studying its interaction with M2 muscarinic receptor. The research was conducted using FAs compounds with known safety and drug compounds that act as agonists or antagonists on M2 muscarinics receptor as reference compounds. The interaction studies carried out included docking and molecular dynamics simulations. The priority of FAs compounds which were used for further evaluation using molecular dynamic simulation were determined based on the number of interactions with key amino acids and the bond free energy values obtained from docking simulation. The conformation obtained from docking simulation was then used as the initial conformation in molecular dynamic simulations. Based on the results of the molecular dynamic simulations of the reference compounds, the threshold Ki value was 0.046 nM and the key amino acids were Tyr104, Tyr403, Cys429, and Ala194. The tested FAs compounds which have Ki value lower than 0.046 nM and show interactions with key amino acids were predicted as potentially unsafe compounds due to their affinities against the receptor, which can provide the same pharmacological effects as the reference compounds. From 40 tested FAs compounds which were evaluated using molecular dynamic simulations, there were 25 FAs compounds that were predicted to be potentially unsafe. Based on overall results, it was concluded that this interaction study against M2 muscarinic reseptor by in silico method has good possibility to be further developed and evaluated as an alternative method for screening the safety of FAs.